2012
DOI: 10.1902/jop.2012.110605
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Status and Metabolic Syndrome in Middle‐Aged Japanese

Abstract: The results of this study suggest that periodontal status, particularly in individuals suspected to have untreated periodontal infection indicated by ≥4 mm PD, is significantly associated with MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 49 publications
6
75
2
5
Order By: Relevance
“…Epidemiological studies, which have reported an association between periodontitis and MetS have been cross-sectional in nature and cannot identify the direction of any effect (Shimazaki et al 2007, Kushiyama et al 2009, Kwon et al 2011, Fukui et al 2012). In the largest population studied from NHANES III the association with severe periodontitis (two sites with CAL 6 mm) was not significant in the whole sample but only in those aged 45 years .…”
Section: Metabolic Syndrome (Appendix S6)mentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies, which have reported an association between periodontitis and MetS have been cross-sectional in nature and cannot identify the direction of any effect (Shimazaki et al 2007, Kushiyama et al 2009, Kwon et al 2011, Fukui et al 2012). In the largest population studied from NHANES III the association with severe periodontitis (two sites with CAL 6 mm) was not significant in the whole sample but only in those aged 45 years .…”
Section: Metabolic Syndrome (Appendix S6)mentioning
confidence: 99%
“…The more accepted criterion of 3 positive components to identify MetS was not used as only 0.8% subjects were affected. Of concern in this and other studies from Japan is the modification of accepted criteria by replacing WC, a measure of abdominal obesity and insulin resistance, with a general measure of adiposity (BMI 25) (Kushiyama et al 2009, Fukui et al 2012) and the use of diabetes as an indicator of glucose intolerance (Shimazaki et al 2007, Kushiyama et al 2009) rather than a confounder in any association.…”
Section: Metabolic Syndrome (Appendix S6)mentioning
confidence: 99%
See 1 more Smart Citation
“…4 It has been discovered that CPD is associated with systemic diseases, such as MetS, [5][6][7] coronary heart disease, 8,9 and CPD is associated with endothelial dysfunction. 10 Because CPD and ED share common risk factors, the epidemiological and pathophysiological linkage between CPD and ED is quite possible.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The metabolic syndrome is also known as Syndrome X, dysmetabolic syndrome, deadly quartet and plurimetabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%